SISTEM INFORMASI PENJUALAN MAKANAN PADA KEDAI BLAST PURWOREJO BERBASIS WEB - Agus Irwan Gunawan; Damar Eko Cahyono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
The problem examined in this study is how to design and make a Food Sales Information System in Purworejo Kedai Blast with an accounting system that has good and appropriate output with the store management needs. The purpose of the designer is that it can help facilitate services to consumers and reports to store owners with the accounting system. This information system was created for food sales at Purworejo Blast Store. The method used in making this system is qualitative with descriptive translation. Data collection techniques used are observation, discourse and documentation. Based on the results of the study it can be concluded that: This system can make it easier to sell food at Kedai Blast Purworejo, checking system makes it possible to prevent the occurrence of the length of service and to calculate the number of production sales that are less accurate and the system can produce output according to accounting calculations.